Development of Prezi-Based Audio-Visual Media to Improve Economics Learning Outcomes for Grade X Students at SMA X - Saor Maruli Hasibuan; Endang Mulyani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study develops Prezi-based audio-visual learning media aimed at improving motivation and economics learning outcomes for Grade X students at SMA X. The primary issue addressed is the low motivation and achievement among students due to the use of monotonous teaching methods and unengaging media. This research distinguishes itself by integrating Prezi’s Zooming User Interface (ZUI) with economics content, aligning with the independent curriculum and the Pancasila student profile. The study follows the Four-D Research and Development (R&D) model, consisting of Define, Design, Develop, and Disseminate phases. Data were collected through needs analysis, expert validation, and a quasi-experimental pretest-posttest control group design. Two classes, each consisting of 36 students, participated in the study. The learning media developed integrates various components such as text, images, charts, animations, and audio explanations, creating a comprehensive and interactive learning experience. The media was validated and found to be suitable, practical, and flexible for classroom use. The experimental group using the Prezi-based learning media saw a significant improvement in their learning outcomes. The average score of this group increased from 43.472 to 86, showing a substantial gain. In contrast, the control group, which used traditional methods, showed a smaller increase in average score, from 43.056 to 66.389. These results indicate that Prezi-based media is an effective tool for enhancing students' motivation and learning outcomes. It provides an innovative and engaging alternative for teachers, making economics content more dynamic and accessible. The study suggests that integrating such audio-visual tools can play a crucial role in improving the quality of learning, fostering both student engagement and academic achievement.